2004
DOI: 10.1073/pnas.0407117101
|View full text |Cite
|
Sign up to set email alerts
|

Finding new components of the target of rapamycin (TOR) signaling network through chemical genetics and proteome chips

Abstract: drug discovery ͉ drug target identification ͉ proteomics ͉ diabetes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
164
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(172 citation statements)
references
References 33 publications
4
164
0
4
Order By: Relevance
“…Overexpression of GTR2 or EGO3 increases rapamycin resistance (Dubouloz et al, 2005), and EGO3 is the target of a synthetic molecule (SMIR4) that promotes rapamycin resistance. Furthermore, transcript profiling suggests that ego3 mutants show considerable similarities to rapamycin treated cells (Huang et al, 2004). These observations strongly suggest that EGOC acts upstream of TORC1.…”
Section: Regulation Of Mtorc1 By Nutrient Abundancementioning
confidence: 75%
“…Overexpression of GTR2 or EGO3 increases rapamycin resistance (Dubouloz et al, 2005), and EGO3 is the target of a synthetic molecule (SMIR4) that promotes rapamycin resistance. Furthermore, transcript profiling suggests that ego3 mutants show considerable similarities to rapamycin treated cells (Huang et al, 2004). These observations strongly suggest that EGOC acts upstream of TORC1.…”
Section: Regulation Of Mtorc1 By Nutrient Abundancementioning
confidence: 75%
“…The basic premise of high-density arraying has since been expanded to create protein arrays for probing protein-protein or protein-small molecule interactions 18,19 , carbohydrate arrays 20 , tissue arrays 21 and smallmolecule arrays 22 . In a twist of the canonical microarraying technique, the cell microarray, nucleic acids are printed in defined locations on a glass slide and used to transfect cells added on top of the microarray 5 .…”
Section: Overexpression Cell Microarraysmentioning
confidence: 99%
“…Protein chips have been used to test for specific protein or nucleic acid binding, and for a variety of biochemical activities, including protein phosphorylation. [77][78][79][80][81][82] The results from these studies have already demonstrated the immense potential of this technology and indicate how it could revolutionize the way we carry out particular types of biochemical analyses.…”
Section: Protein Chips or Proteome Microarraysmentioning
confidence: 95%